A Genealogy of the Ridiculous: From 'Humours' to Humour - Goldberg, Brenda (Outlines. Critical Practice Studies, 1999)
We tend to take the phenomenon of humour for granted, seeing it for the most part as something innately and fundamentally human. However we might go even further than this, and say that the phenomenon of humour is perceived as an essential part of what makes us human. In this respect, philosophers and theorists as wide apart as Aristotle and the French, feminist Julia Kristeva (1980; also see Goldberg, 1999a) have regarded a baby's ability to laugh as one of the earliest signs of the separation of 'self' from 'other', a reciprocal process deemed to be crucial to the formation of a separate identity. However, although the general importance of humour might be agreed amongst researchers, what theoretical position one takes will have a profound effect on how one approaches and analyses humour. In much psychological research the focus tends to be on how humour works, i.e., syntax, semantic categories, sex differences, personality types, etc., and one finds a frustrating neglect of what is actually meant by the term 'humour' in terms of history and emergences. Consequently, an important question tends to go unchallenged: Is humour some unproblematic innate human ability, or, a socially defined concept that has changed and mutated alongside our understanding of what is means to be person? In an attempt to grapple with this question, the following genealogical account is less concerned with fathoming out how humour works than with relating it to notions of human subjectivity, or how theories of humor have informed and reflected social constructs of what it means to be a 'subject'.